If a/(b+c) = b/(c+a) =
c/(a+b) = r, then r can not take any value except__

Solution:

(1) 1/2
(2) -1 (3) ½ or -1 (4)
-1/2 or -1

For Answer
Click on "Read more" below:

Solution:

a/(b+c)
= b/(c+a) = c/(a+b) = r

=>
a = r(b+c); b = r(c+a); c = r(a+b);

=>
a+b+c = r(b+c)+r(c+a)+r(a+b)

=>
a+b+c = 2r(a+b+c)

=>
(2r-1)(a+b+c) = 0

=>
2r-1 = 0 (or) a+b+c = 0

=>
r = ½ --(1)

a+b+c
= 0 => b = -(c+a) => b/(c+a) = -1 => r = -1 ---(2)

From
(1) and (2), r = ½ or -1

**Answer (3)**
## No comments:

## Post a Comment